2016
DOI: 10.1039/c6cs00442c
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon excitation nanoparticles for photodynamic therapy

Abstract: Two-photon excitation (TPE) nanoparticle-based photosensitizers (PSs) that combine the advantages of TPE and nanotechnology have emerged as attractive therapeutic agents for near-infrared red (NIR) light excited photodynamic therapy (PDT) for cancer treatment. TPE PDT is characterized by nonlinear absorption of two relatively low-energy photons of NIR light with the resulting emission of high-energy visible light. This high-energy light can sensitize oxygen to produce cytotoxic reactive oxygen species (ROS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
308
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 494 publications
(308 citation statements)
references
References 178 publications
0
308
0
Order By: Relevance
“…Several inorganic NPs, including metallic NPs (Wang et al, 2017), inorganic nanocrystals (Ipe et al, 2005; Wang et al, 2015) and magnetic NPs, have been reported to have sizable effects on the ROS population, thus representing an interesting strategy for photothermal therapies (Ye and Chen, 2016; Dayem et al, 2017). Among carbon-based materials, carbon nanotubes, graphene and polymer nano-bioconjugates can also sustain photo-thermal stimulation (Miyako et al, 2014; Chechetka et al, 2016; Lyu et al, 2016; Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several inorganic NPs, including metallic NPs (Wang et al, 2017), inorganic nanocrystals (Ipe et al, 2005; Wang et al, 2015) and magnetic NPs, have been reported to have sizable effects on the ROS population, thus representing an interesting strategy for photothermal therapies (Ye and Chen, 2016; Dayem et al, 2017). Among carbon-based materials, carbon nanotubes, graphene and polymer nano-bioconjugates can also sustain photo-thermal stimulation (Miyako et al, 2014; Chechetka et al, 2016; Lyu et al, 2016; Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[4] As far as PDT is concerned, oxygen is known to be essential in the process of singlet oxygen generation, while tumor hypoxia microenvir-onment considerably limits the therapeutic effect of PDT. [9] However,h ow to combine these techniques into one system for solving both problems PDT face is still ag reat challenge. [7] Researchers have proposed many solutions to solve these problems,i ncluding increasing oxygen supply inside tumor to enhance PDT efficiency, [8] applying two-photon excitation (TPE) to improve treatment depth in PDT.…”
mentioning
confidence: 99%
“…This technique combine the advantages of TPE near-infrared (NIR) photosensitizers and nanotechnology and has been reviewed by Shen et al [466]. The absorption of two relatively low-energy NIR photons will enable the emission of high-energy photons in the visible spectrum, which in its turn will sensitize oxygen producing singlet oxygen and reactive oxygen species (ROS) able to kill targeted cancer cells due to its cytotoxic effect.…”
Section: Multimodal Therapy Options For Prostate and Breast Cancermentioning
confidence: 99%